Exploring the Salutogenic University: Searching for the Triple Point for the Becoming-Caring-Teacher Through Collaborative Cartography - Kinchin, Ian M.; Derham, Cathrine; Foreman, Charlotte; McNamara, Anna; Querstret, Dawn (Pedagogika, 2023)
This paper offers a perspective on ‘care’ as a component in the identity of successful university teachers. Three key lines of flight within this assemblage (care, pedagogic health, and salutogenesis) are examined here. In combination, they may offer a response to hegemonic neoliberal discourses that typically divert academics from enacting their professional values. A ‘triple point’ is hypothesised, at which the three lines would be found to co-exist, without border or barriers.